BOTABEK SHUTTLE EXPRES: SUATU USULAN SOLUSI UNTUK PERMASALAHAN TRANSPORTASI JABODETABEK - Susilo, Budi Hartanto (Jurnal Transportasi, 2014)
The traffic congestion during rush hours in Jakarta has exceeded the limits the patient of road users. As a result, the discipline and respect of road users disappear and the number of drivers violating traffic regulation is increasing. One solution proposed in this study is to develop business in the field of mass transit in the Botabek region, tentatively named Botabek Shuttle Express. To support the operation of Botabek Shuttle Express, it is necessary to do a comprehensive study. Results from this study suggest the potential number of private vehicles willing to move to Botabek Shuttle Express is as much as 47 485 vehicles, the number of people willing to change into Botabek Shuttle Express is approximately 73 151 people, and the required number of BSE fleet with a seating capacity of 30 is 1,219 buses. Keywords: traffic congestion, rush hour, mass transport, private vehicles  Kemacetan lalulintas Jakarta pada jam sibuk sudah melampaui batas kesabaran pengguna jalan. Akibatnya disiplin dan etika berlalulintas hilang dan ketidakpatuhan pengguna jalan kepada peraturan semakin meningkat. Suatu solusi yang diusulkan pada studi ini adalah melakukan mengembangkan usaha di bidang angkutan massal di wilayah Botabek, yang sementara ini diberi nama Botabek Shuttle Express. Guna mendukung beroperasinya Botabek Shuttle Express perlu dilakukan suatu kajian yang komprehensif. Hasil kajian ini menunjukkan adanya potensi jumlah kendaraan pribadi yang pindah ke Botabek Shuttle Express sebanyak 47.485 kendaraan, jumlah orang yang pindah ke Botabek Shuttle Express sebanyak 73.151 orang, serta jumlah armada BSE yang dibutuhkan sebanyak 1.219 bus dengan kapasitas tempat duduk 30. Kata-kata kunci: kemacetan lalulintas, jam sibuk, angkutan massal, kendaraan pribadi